Chlorosulfonic Acid Supported Piperidine-4-carboxylic Acid (PPCA) Functionalized Fe3O4 Nanoparticles (Fe3O4-PPCA): The Efficient, Green and Reusable Nanocatalyst for the Synthesis of Pyrazolyl Coumarin Derivatives under Solvent-Free Conditions - Habibzadeh, Setareh; Ghasemnejad-Bosra, Hassan; Haghdadi, Mina; Heydari-Parastar, Soheila (Combinatorial Chemistry & High Throughput Screening, 2019)
Background: In this study, we developed a convenient methodology for the synthesis of coumarin linked to pyrazolines and pyrano [2,3-h] coumarins linked to 3-(1,5-diphenyl-4,5- dihydro-1H-pyrazol-3-yl)-chromen-2-one derivatives using Chlorosulfonic acid supported Piperidine-4-carboxylic acid (PPCA) functionalized Fe3O4 nanoparticles (Fe3O4-PPCA) catalyst. Materials and Methods: Fe3O4-PPCA was investigated as an efficient and magnetically recoverable Nanocatalyst for the one-pot synthesis of substituted coumarins from the reaction of coumarin with a variety of aromatic aldehydes in high to excellent yield at room temperature under solvent-free conditions. The magnetic nanocatalyst can be easily recovered by applying an external magnet device and reused for at least 10 reaction runs without considerable loss of reactivity. Results and Conclusion: The advantages of this protocol are the use of commercially available materials, simple and an inexpensive procedure, easy separation, and an eco-friendly procedure, and it shows good reaction times, good to high yields, inexpensive and practicability procedure, and high efficiency.
Keywords: solvent-free conditions